First record of a melanistic Italian wall lizard (Podarcis sicula) in Slovenia - Krofel, Miha (Natura Sloveniae, 2005)
The article presents the discovery of a melanistic male Italian Wall Lizard (Podarcis sicula) from the vicinity of Padna in Koprsko primorje region (UTM UL93, 220 m a.). This is the first record of a melanistic Italian Wall Lizard in Slovenia.
Keywords: Ecosystem; Ekosistem; Kuščarji; Lizards; Melanini; Melanins; melanizem; plazilci; primorska kuščarica; reptile; Slovenia; Slovenija